Evaluating the effectiveness of an adult entrepreneurship training programme in Namibia. - Bennett, Margaret Rosamund (My University, 2013)
Small and Medium Enterprises play an important role in emerging economies with its capacity to create employment opportunities and hence contributing to a country’s GDP. The training of adult entrepreneurs however remains a challenge as there is no consensus as to the components that should be included in such training initiatives. This study aims to evaluate an adult entrepreneurship programme in terms of its content, delivery methods and outcomes concurrent to the perceived values and challenges experienced by entrepreneurs in the Namibian business community. A cross-sectional research approach was followed, with surveys distributed to a convenience sample of Entrepreneurs (N= 102) who participated in the training programme. The results overall showed that the respondents benefitted to a large extent from the training programme. The training programme contributed to improved business performance, an increased client base for the respondents, improved work attitude and overall entrepreneurial skills. Various challenges are faced by entrepreneurs, of which the perceived values of the Namibian market plays an important role. The research presents an integrated framework by combining the elements of the macro, meso and micro environments to enable the effective transfer and application of knowledge for adult entrepreneur trainees in their respective businesses. Recommendations are made.
Thesis presented in partial fulfillment of the requirements for the degree of Master of Leadership and Change Management at the NUST
Keywords: Adult entrepreneurship training programme - Namibia; Entrepreneurship training programme - Namibia; Master's theses - Namibia; Adult training programme - Namibia; NUST - Master's theses, 2013